2010
DOI: 10.1002/ejlt.200900148
|View full text |Cite
|
Sign up to set email alerts
|

Oil quality characteristics of irradiated sunflower and maize seed

Abstract: The characteristics of oils extracted from gamma-irradiated sunflower (Halianthus annuus) and maize (Zea mays) seeds at absorbed doses of 2, 4, 6, 8, and 10 kGy were investigated. Gamma irradiation did not affect the lipid, protein, fiber, and ash contents of neither sunflower nor maize seeds significantly ( p>0.05). No significant changes were observed for the values of refractive index and density between the control and irradiated sunflower and maize oils. Peroxide value, acid value, para-anisidine value, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Meanwhile, j-and ô-tocopherols were detected in small amounts with contributions of 8.81-8.95 mg kg"^ and 2.32-2.80 mg kg"\ respectively in both the varieties of almond oils. Overall, the tocopherol values were decreased by increasing the irradiation dose and the trend was in accordance with the studies of Bhatti et al (2010) and Yaqoob et al, (2010) who studied a decreasing trend in the amounts of total tocopherols of irradiated sunflower, maize and peanut oil up to absorbed doses of 10 kGy. The decreasing trend in the tocopherol contents of irradiated oil samples might be linked to the degradation of these antioxidant componenets during irradiation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, j-and ô-tocopherols were detected in small amounts with contributions of 8.81-8.95 mg kg"^ and 2.32-2.80 mg kg"\ respectively in both the varieties of almond oils. Overall, the tocopherol values were decreased by increasing the irradiation dose and the trend was in accordance with the studies of Bhatti et al (2010) and Yaqoob et al, (2010) who studied a decreasing trend in the amounts of total tocopherols of irradiated sunflower, maize and peanut oil up to absorbed doses of 10 kGy. The decreasing trend in the tocopherol contents of irradiated oil samples might be linked to the degradation of these antioxidant componenets during irradiation.…”
Section: Resultssupporting
confidence: 89%
“…The decreasing trend in the tocopherol contents of irradiated oil samples might be linked to the degradation of these antioxidant componenets during irradiation. Furthermore, due to the thermal oxidation of the oil, the tocopherol values may also decrease (Yaqoob et al, 2010). The effect of gamma radiations on the tocopherol contents of the oils from both almond varieties was similar.…”
Section: Resultsmentioning
confidence: 85%
“…The effects of irradiation on edible vegetable oils depend on the chemical composition of oils and irradiation conditions such as irradiation dose, dose rate, etc . Lately, research has focused on quantifying the levels of phytochemicals found in vegetable oils after irradiation processing . Our preliminary tests on irradiation of sea buckthorn oil showed that the antioxidant activity can be affected by increasing the irradiation dose while the antimicrobial activity was unaffected.…”
Section: Introductionmentioning
confidence: 92%
“…Also, the irradiation doses appropriate for a food are a compromise between several objectives and constraints. The effects of irradiation on edible vegetable oils depend on the chemical composition of oils and irradiation conditions such as irradiation dose, dose rate, etc . Lately, research has focused on quantifying the levels of phytochemicals found in vegetable oils after irradiation processing .…”
Section: Introductionmentioning
confidence: 99%
“…No previous data were available on the effect of microwave treatment on the fatty acid composition of oil for comparison. However, Yaqoob et al reported that the effect of gamma irradiation on the fatty acid composition of oil extracted from irradiated sunflower seeds was significant (Yaqoob, et al, 2010). …”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%